Increasing the Solar Panel Efficiency after Production by Alternate Methods - Lenin Rakesh, N.; Srinath, R.; Thiagu, B.; Hari Govindhan, R.L. (International Journal of Psychosocial Rehabilitation, 2019)
The objective of this project is to increase the efficiency of the solar panel by using alternative methods and to utilise the maximum energy from solar energy. Generally, the efficiency of the solar panel is about 16%. The solar energy is being wasted in enormous amounts without converting it into electricity. There are different ways to increase the efficiency of solar panels. Water or any medium is used to decrease the temperature of the solar panel and maintain it at ambient temperature, which will help to increase the efficiency of the solar panel. The second method is using a mirror at an appropriate angle, which will increase the intensity of the solar rays reflecting on the solar panel and increase the efficiency. The other method is to use a convergence lens, which will help to concentrate the solar rays on the solar panel, and the efficiency increases. The common method is to have periodic rotation of the solar panel according to the sun movement, which will increase the time period of production for the solar panel.